Nursing care in ophthalmologic surgeries: experience report (Research, Society and Development, 2021)
Objective: describe the experience lived by nurses in an ambulatory surgical center during the phases of care of patients undergoing ophthalmologic surgeries. Method: this is a descriptive study, of the experience report type, narrated by nurses with professional experience in an ambulatory surgical center that provides care to patients in the perioperative period of ophthalmologic surgeries. The field of study is a public university hospital located in the South region of Brazil. Results: on the day the surgery is scheduled, the patient is admitted to the surgical center accompanied by a guardian over 18 years of age. The Nursing technician performs the first care, putting on the identification bracelet with full name and medical record number, checking vital signs, weight and height, collecting information such as allergies and fasting time, use of any device, orthosis or mobile prosthesis. The surgical team performs the laterality marking; the nurse performs the anamnesis and the anesthesiologist performs the patient's evaluation. The nursing team accompanies the patient during the trans-operative period. At the end of the procedure, the patient is taken to the recovery room, where he/she remains until his/her full recovery. When able to be discharged from the hospital, a home care plan is implemented so that the patient can perform the care. Conclusion: the nurse is a facilitator of the surgical process and must implement strategies based on technical-scientific knowledge, complying with quality and safety standards, bringing greater quality of the assistance provided to Nursing care, stimulating the development of critical thinking related to the theme.